Optimalization of Gen-Z Quality In Candijati Village Becoming Young Generation of Work - Falahi, Asa; Rashati, Dewi; R, Rosida; Rohman, Anies (Nanggroe: Jurnal Pengabdian Cendikia, 2025)
The PIK-R youth organization in Candijati Village is not new. However, it is felt to be less active in carrying out activities that should be the purpose of forming the organization. Awareness of the importance of the role of youth in realizing village welfare must be revived. This service aims to provide motivation to teenagers in Candijati Village to be more optimal and effective in managing the PIK-R organization. The implementation of the service is carried out by providing socialization and training to the PIK-R administrators of Candijati Biting Village, Jember Regency, East Java Province. The material provided is material related to leadership and organizational management issues. Through this service activity, it can provide skills for the PIK-R administrators of Candijati Village in managing the organization, forming a management structure, fostering leadership talent and understanding related to early marriage which has a negative effect on teenagers. The programs at the growth stage implemented in PIK-Teenagers in Candijati Village have proven successful in increasing students' understanding of organizational management, reproductive health and reducing the risks of early marriage.